2003
DOI: 10.1172/jci200317664
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic role for cardiac myocyte apoptosis in heart failure

Abstract: Heart failure is a common, lethal condition whose pathogenesis is poorly understood. Recent studies have identified low levels of myocyte apoptosis (80–250 myocytes per 105 nuclei) in failing human hearts. It remains unclear, however, whether this cell death is a coincidental finding, a protective process, or a causal component in pathogenesis. Using transgenic mice that express a conditionally active caspase exclusively in the myocardium, we demonstrate that very low levels of myocyte apoptosis (23 myocytes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
298
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(322 citation statements)
references
References 24 publications
19
298
0
5
Order By: Relevance
“…A similar PUMAdependency of cardiomyocyte apoptosis has been found in ischemia-reperfusion model of cultured cardiomyocyte [36]. This pathway would also involve BCL2-protein interaction [37,38], BAX/BAK-induced MOMP [39] and activation of initiator and activator caspases [24,39,40] similar to the above presented canonical intrinsic apoptosis in cancer cells. Likewise, invocation of the extrinsic apoptosis program by DOX via FAS-L or TRAIL ligands has also been detected in cardiomyocytes similar to cancer cells [41,42], potentially attaining robust caspase-3 activation by invoking MOMP (type II cells, Fig 1).…”
Section: Pathways Of Cardiomyocyte Apoptosis Relevant To Dox -Inducedsupporting
confidence: 67%
See 1 more Smart Citation
“…A similar PUMAdependency of cardiomyocyte apoptosis has been found in ischemia-reperfusion model of cultured cardiomyocyte [36]. This pathway would also involve BCL2-protein interaction [37,38], BAX/BAK-induced MOMP [39] and activation of initiator and activator caspases [24,39,40] similar to the above presented canonical intrinsic apoptosis in cancer cells. Likewise, invocation of the extrinsic apoptosis program by DOX via FAS-L or TRAIL ligands has also been detected in cardiomyocytes similar to cancer cells [41,42], potentially attaining robust caspase-3 activation by invoking MOMP (type II cells, Fig 1).…”
Section: Pathways Of Cardiomyocyte Apoptosis Relevant To Dox -Inducedsupporting
confidence: 67%
“…Moreover, in a transgenic mouse model with constitutively active caspase-8 only a small detectable elevation of apoptosis only 23 myocytes per 10 5 cells sufficed to induce a dilated cardiomyopathy phenotype [24]. Importantly, this amount is four-to tenfold lower than that measured in three independent studies of failing human hearts.…”
Section: Evidence For Cardiomyocyte Apoptosis In Dox-induced Dcmmentioning
confidence: 86%
“…Endoplasmic reticulum stress and heart failure Various stimuli, such as hypoxia [132,133] , Ang II stimulation [134] , oxidative stress [135] and inflammatory factors [136] , have been proposed to trigger ERS during heart failure (HF). However, the role of ERS in heart failure is still in dispute.…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%
“…Using this method with a former version of homodimerization-regulated caspase, Wencker et al have recently demonstrated that myocyte apoptosis can be a causal mechanism of heart failure. 53 Mouse models for different human disorders in which apoptosis is involved could also be generated using such a strategy. For example, Mallet et al 54 recently used a similar approach with caspase 3 specifically expressed in the liver of transgenic mice.…”
Section: Fkc8-driven Cell Suicide Is a Bona Fide Apoptotic Process Anmentioning
confidence: 99%